A NEW ROMAN REPUBLICAN HOARD IN PRE-ROMAN DACIA (ROMANIA). A PRELIMINARY NOTE. THE MINTING PLACE OF A HYBRID TYPE - Cristian Gazdac; Ghemis Călin; Lucian Barbu-Tudoran (Journal of Ancient History and Archaeology)
The discovery of a new hoard consisting of Roman republican denarii has led to the re-opening of an old debate on the copying/imitation phenomenon of Republican denarii in pre-Roman Dacia. A case study is presented in this study on one piece from this hoard. At first sight, the coin looks as a genuine denarius, but at a closer look reveals not only that the piece is a hybrid but also that between the two prototypes of obverse and reverse was a period of 25 years. Despite the widespread phenomenon of copying Roman republican denarii in pre-Roman Dacia, the metal analyses of this coin revealed the absence of the lead (Pb) from its composition. A metal that is always present in the other cases of copies or imitations of Roman republican denarii found in Dacia.